Studies bearing on: (1) The nutrition of Bantu infants and young children and (2) The metabolism of calcium and iron by Bantu children and adults - Walker, Alexander Robert Pettigrew (Department of Paediatrics and Child Health, 2020)
The continent of Africa is inhabited by about 270 million persons of whom about 60 million are Bantu. They dwell mainly south of the Equator. South African Bantu number about 11 million persons, of whom under a third are urbanised, and over a third each work on farms of Whites or live in the Native Reserves. These local Bantu are comprised of several ethnic groups, the largest of which are Zulu and Xhosa. While some communities of rural Bantu still live in a primitive manner. others, mainly in urban areas, tend progressively to adopt a westernised type of diet and manner of life. The Bantu may therefore be observed in all stages of transition, in relation to patterns of diet, metabolism, and pathology. The studies undertaken and to be described concern primarily the nutrition of infants and children, the prevalence of certain deficiency diseases, and the handicap imposed by parasitism on nutritional state and other parameters.